Professional training and critical method: the experience of UFPA-Breves in Marajó (Temporalis, 2026)
This article aims to analyze the connection between the critical-dialectical method and professional training in the Social Work course at the Federal University of Pará in Breves (FACSS-Breves), based on the Professional Ethical-Political Project (PEPSS). The research, of a qualitative and quantitative nature, was grounded in historical-dialectical materialism and combined documentary analysis of the Course Pedagogical Project with semi-structured interviews conducted in 2024 with eight graduates. The results demonstrate that this connection is realized through an intentional curriculum, which includes courses on regional contextualization, a sequence on the historical and theoretical foundations of the profession, and supervised internships. The graduates' perceptions show that the training they received qualified them to perform critical readings of reality, challenge institutional limits, and work with an ethical-political commitment to the working class in the Marajó Archipelago. It is concluded that the FACSS-Breves curriculum is crucial for the consolidation of a critical Social Work practice in the Amazon, even though structural challenges persist.
Keywords: Professional training; Ethical-political project; Dialectical historical materialism; Social work; Marajó